NILAI NILAI PENDIDIKAN KARAKTER SURAH AL-BAQARAH AYAT 155-157 - Imam Bohri Idris; Burhanuddin Ridlwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of character education in shaping students’ personalities with noble morals amid various challenges of life. The Qur’an, as the main source of Islamic teachings, contains many character education values that can serve as a foundation for daily life. One of the verses containing these values is Surah Al-Baqarah verses 155–157, which explain life’s trials and the attitudes of believers in facing them. This study aims to examine and describe the character education values contained in Surah Al-Baqarah verses 155–157 and their relevance to life and Islamic education. The research method used in this study is library research with a qualitative approach and the maudhu’i (thematic interpretation) method. The data were obtained from the Qur’an, tafsir books, books, journals, and other scientific sources relevant to character education. The data analysis technique was conducted by collecting verses related to the themes of life trials and human character, then analyzing them deeply to obtain a comprehensive understanding. The results of the study show that Surah Al-Baqarah verses 155–157 contain character education values such as patience and sincerity in facing life’s trials. The value of patience is reflected in steadfastness, not giving up easily, and having trust in Allah SWT. Meanwhile, the value of sincerity is reflected in accepting Allah’s decrees wholeheartedly and surrendering oneself completely to Him. These two values play an important role in forming individuals who are strong, calm, and possess noble character. In conclusion, the character education values contained in Surah Al-Baqarah verses 155–157 are highly relevant to be applied in life and education. These verses can serve as a foundation in shaping students’ character so that they possess strong faith, patience, sincerity, and the ability to face various life challenges wisely in accordance with Islamic teachings.